Effect of bis-1,4-Dihydropyridine in the Kidney of Diabetic Rats - Raquel Gómez-Pliego; Jaime Gómez-Zamudio; Benjamín Velasco-Bejarano; Maximiliano Ibarra-Barajas; Rafael Villalobos-Molina (Elsevier, 2013)
The in vivo effectiveness of 4-dihydropyridine (bis-1,4-DHP), a new calcium-channel blocker, as a nephroprotector in isolated perfused kidney was evaluated by determining its effects on parameters associated with renal injury in diabetic rats. Diabetes in male Wistar rats, control, diabetic, control + bis-1,4-DHP, and diabetic + bis-1,4-DHP, was induced by a single administration of STZ (55 mg×kg−1, i.p.). In the drug-treated groups, treatment with bis-1,4-DHP (10 mg×kg−1×day−1) started one week before diabetes induction; bis-1,4-DHP was dissolved in DMSO (0.3%) and suspended in drinking water with carboxymethyl cellulose (3%). Parameters evaluated were body weight, blood glucose, albuminuria, proteinuria, creatinine, urea excretion, kidney's weight / body weight ratio, and kidney perfusion pressure in all rat groups at different times of diabetes (2, 4, 6, and 10 weeks). Kidney weight of diabetic rats significantly increased vs. control, control + bis-1,4-DHP, and diabetic + bis-1,4-DHP rats at different times of diabetes. The ratios % kidney weight / 100 g body weight were different between control, control + bis-1,4-DHP, and diabetic + bis-1,4-DHP rats vs. diabetic rats (P < 0.05). Kidney perfusion pressure was decreased by diabetes, while it was partially recovered by bis-1,4-DHP treatment in response to phenylephrine. Bis-1,4-DHP had a tendency to decrease hyperglycemia vs. diabetic rats, even though glycemia was too high as compared with controls, and it ameliorated albuminuria, creatinine, and urea excretion, suggesting a favorable effect on renal haemodynamics. Bis-1,4-DHP, by inhibiting Ca2+ entrance, induced vasodilation in renal vascular bed and thus may have a nephroprotective effect against diabetes-induced renal dysfunction, but does not have significant impact on hyperglycemia. Keywords:: bis-1,4-dihydropirydine derivative, calcium-channel blocker, nephoprotector, diabetes, kidney